Analisis Perangkat Lunak Penilaian Digital Pertandingan Pencak Silat Menggunakan ISO 9126 - Reza Prasetyo Aji (Universitas Indraprasta PGRI Jakarta, 2021)
This study aims (1) to know the quality of software possessed by eventsilat.com aplications, which is good or bad according to ISO 9126, (2) to know how to measure the quality characteristics of functionality, reliability, usability, efficiency, maintainability, and portability on eventsilat.com applications and (3) to know the quality of the last result of functionality, reliability, usability, efficiency, maintainability, and portability on eventsilat.com aplications based on ISO 9126. The analysis was conducted through a test case of each ISO 9126 characteristic. The results of this study show (1) the eventsilat.com digital assessment applications as a whole get good interpretation according to ISO 9126 with a value of 3.09 (2) How to measure the quality characteristics of functionality, reliability, usability, efficiency, maintainability, and portability at eventsilat.com aplications is by measuring the interpretation value using Likert scale of each character and sub character ISO 9126 and then test case, and (3) the quality of the last result of functionality is very good with the value of 3,26, the quality of reliability is good with a value of 2.74, usability quality is very good with a value of 3.52, the quality of efficiency is good with a value of 2.91, the quality of maintainability is good with a value of 2.99, and quality portability is good with value of 3.09.